Prevalence of foot posture deformities using foot posture index in various intensive care unit nurses - Sawant, Aditi R.; Akash, Aishwarya (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aims to determine the prevalence of foot posture deformities among various intensive care unit nurses using the Foot Posture Index. Nurses working in ICUs often face long hours of standing and walking, which can contribute to the development of foot-related problems. Understanding the extent of these deformities can contribute to the development of preventive measures, such as ergonomic interventions and targeted exercises, to mitigate the risk of foot-related issues. Methods: A study was conducted among 159 nurses from various Intensive Care Units. The Foot Posture Index, a validated tool for assessing foot posture was used to assess foot deviations in nurses. Results: In total159 participants were evaluated, with 6 (4%) being males and 153 (96%) being females. The mean age of the participants was (Mean=40.67) and standard deviation (SD=9.6). Prevalence percentage of foot posture deviations were found to be bilateral as demonstrated by Foot Posture Index. Out of 159 participants 43% participants had pronated foot, 14% participants had highly pronated foot, 16% participants had supinated foot, 7% had normal highly supinated foot posture and 20% participants had normal foot. Conclusions: To conclude the present study, pronated foot posture was the most common foot deviation. Moreover, when BMI was compared with the pronated foot deviation, there was a positive association between pronated foot and the nurses who were overweight.